A method for hydrocracking of a wax oil feedstock
Patent Information
- Application Number
- CN202510266714.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-07
- Publication Date
- 2026-09-08
AI Technical Summary
[0006]综上所述,现有技术以多种不同种类分子筛复合材料作为加氢裂化催化剂的酸性载体,利用其差异化的孔道和酸性特征调变催化剂活性,但也普遍存在着馏分油产品产量和质量不能兼顾的问题,其本质原因在于重油原料中稠环芳烃较高,导致稠环芳烃大分子在加氢裂化催化剂中传质、反应受限情况变严重,容易发生深度裂解不够、产品选择性变差等问题,具有稠环烃分子强开环能力同时兼具高产品质量的高效加氢裂化催化剂亟待开发
[0042] The BY heteroatom molecular sieve in the hydrocracking catalyst provided by this invention possesses characteristics such as a high Brønsted acid/Low acid ratio, a high proportion of moderately strong acids, high crystallinity, and abundant mesoporous channels, all of which are highly beneficial for the ring-opening conversion of polycyclic aromatic hydrocarbons in heavy oil feedstocks. The hydrocracking catalyst prepared by this invention exhibits advantages such as high reactivity, high product liquid yield, low hydrogen consumption, high aromatic potential in heavy naphtha, high smoke point in jet fuel, and low BMCI value and dry point in tail oil during vacuum oil hydrocracking.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of hydrocracking, specifically relating to a hydrocracking method for wax oil feedstock. Background Technology
[0002] Hydrocracking technology is characterized by its strong adaptability to feedstocks, high flexibility in production operations and product formulations, and high product quality. It can directly convert various heavy and low-quality feedstocks into high-quality jet fuel, diesel, lubricating oil base oil feedstocks, and feedstocks for ethylene production from naphtha and tail oil steam cracking, which are in high demand in the market. It has become one of the important technologies in modern oil refining and petrochemical industries. However, due to the deterioration of crude oil quality year by year, the significant increase in imported high-sulfur crude oil, and the adoption of crude oil vacuum distillation technology by refineries to improve economic efficiency, the dry point of vacuum distillate oil has increased, its density has increased, and it contains more and more large-molecule cyclic hydrocarbon components. All of these have placed new demands on hydrocracking catalysts with strong ring-opening capabilities.
[0003] CN118162208A discloses a hydrocracking catalyst, comprising a support and rare earth metal and heteropolyacid metal active components supported on the support, wherein the catalyst has a specific surface area of 337-355 m². 2 ·g -1 The pore size is 0.40-0.46cm. 3 ·g -1 The invention also discloses its preparation method and applications. The supported carbon aerogel Y / ZSM-35 / NU-87 composite molecular sieve used in this invention accelerates the breaking and formation of Si-O-Si bonds during the initial framework formation process using hydroxyl radicals. This facilitates the introduction of carbonates into the molecular sieve framework, achieving in-situ generation of mesopores and promoting the interaction between the support and the active component. The impregnation solution prepared using a heteropolyacid containing an active metal and a complexing agent can effectively regulate the active phase structure, forming highly dispersed type II phase hydrogenation active centers, significantly improving catalyst activity.
[0004] CN115646540A discloses a composite hydrocracking catalyst and its preparation method. The composite hydrocracking catalyst is composed of catalyst A and catalyst B in a certain mass ratio. Catalyst A uses Y molecular sieve and alumina as supports, and Group VIII and Group VIB metals as active metal components, with an alumina content of 50-65 wt%, a Y molecular sieve content of 10-40 wt%, and an active metal component content of 10-35 wt%. Catalyst B uses Beta molecular sieve and alumina as supports, and Group VIII and Group VIB metals as active metal components, with an alumina content of 50-70 wt%, a Beta molecular sieve content of 15-40 wt%, and an active metal component content of 10-30 wt%. The composite hydrocracking catalyst provided by this invention is used to prepare transformer oil, solving the problem of the inability to simultaneously convert alkane and aromatic hydrocarbons.
[0005] CN117753473A discloses a method for preparing a bulk hydrocracking catalyst, comprising: (1) adding a solution containing W and Mo and a sodium aluminate solution in parallel to a reaction vessel for a gelation reaction, and adding an organic auxiliary agent P1 after the reaction; (2) adding a Ni-containing solution and a precipitant dropwise to the reaction slurry obtained in step (1), aging the obtained slurry, and adding an Al-containing solution in 2 to 8 portions during the aging process, and adding an organic auxiliary agent P2 and a β-molecular sieve slurry after aging, mixing evenly, and filtering the obtained slurry; (3) subjecting the material obtained in step (2) to a first drying, rolling, molding, and washing, and then to a second drying and calcination to obtain a hydrocracking catalyst. The hydrocracking catalyst prepared by this invention has excellent isomerization properties and aromatic conversion ability, and is suitable for application in the hydrocracking process for producing specialty oils and lubricating oil base oils.
[0006] In summary, existing technologies use various types of molecular sieve composite materials as acidic supports for hydrocracking catalysts, utilizing their differentiated pore structures and acidic characteristics to modulate catalyst activity. However, they generally suffer from a mismatch between the yield and quality of distillate oil products. The fundamental reason for this is the high content of polycyclic aromatic hydrocarbons (PAHs) in heavy oil feedstocks, which severely restricts the mass transfer and reaction of large PAH molecules in hydrocracking catalysts, leading to insufficient deep cracking and poor product selectivity. Therefore, highly efficient hydrocracking catalysts with strong ring-opening capabilities of PAH molecules and high product quality are urgently needed for development. Summary of the Invention
[0007] To address the shortcomings of existing technologies, this invention provides a method for hydrocracking wax oil. This method offers advantages such as high reactivity, high product liquid yield, low hydrogen consumption, high aromatic potential of heavy naphtha, high smoke point of jet fuel, and low BMCI value and dry point of the tail oil.
[0008] A method for hydrocracking wax oil, wherein the wax oil feedstock is treated with a hydrorefining catalyst and then reacted under the action of a hydrocracking catalyst, wherein the hydrocracking catalyst contains 10%-50%, preferably 20%-40% BY heteroatom molecular sieve, based on its weight.
[0009] In the method of this invention, the wax oil raw material includes atmospheric pressure wax oil and vacuum pressure wax oil, preferably vacuum pressure wax oil; the properties of the wax oil raw material are: density range 0.85-0.95 g / cm³. 3 Distillation range 300℃-600℃, sulfur content 1.0%-3.0%, nitrogen content 500ppm-2000ppm, BMCI value 40-50.
[0010] In the method of this invention, the hydrorefining catalyst can be any type of commercial catalyst available in the prior art, or it can be prepared according to common knowledge in the field, as long as it can achieve the purpose of hydrorefining the wax oil feedstock. Specifically, in this invention, the hydrorefining catalyst is one or more of the commercial hydrorefining catalysts with the brand names FF-36, FF-46, and FF-66 developed by Sinopec (Dalian) Petrochemical Research Institute Co., Ltd.
[0011] In the method of the present invention, the properties of the hydrorefined oil obtained after hydrorefining of wax oil raw material are as follows: nitrogen content <50ppm, preferably <20ppm; sulfur content <300ppm, preferably <200ppm.
[0012] In the method of this invention, the hydrorefining reaction conditions can adopt the reaction conditions for the hydrorefining of wax oil that are known in the prior art. Specifically, in this invention, the reaction conditions in the hydrorefining reaction zone are: reaction pressure 10MPa~20MPa, preferably 12MPa~16MPa; reaction temperature 350℃~420℃, preferably 380℃~400℃; and the volume hourly space velocity of the hydrorefining catalyst 0.5h⁻¹. -1 ~1.5h -1 0.8h is preferred -1 ~1.2h -1 The hydrogen-to-oil volume ratio is 500-1500, preferably 800-1200.
[0013] In the method of the present invention, the properties of the BY heteroatom molecular sieve are as follows: the silicon-to-aluminum ratio (SiO2 / Al2O3 molar ratio) is 5-20, preferably 8-15; the boron content, based on the mass of oxides, is ≤5.0%, preferably ≤3.0%, and more preferably 0.5-2%.
[0014] In the method of the present invention, the hydrocracking catalyst contains 15%-35%, preferably 20%-30%, of hydrocracking active metal (calculated as metal oxide) based on its weight.
[0015] In the method of the present invention, the hydrogenation active metal is selected from Group VIII and / or Group VIB metals, wherein the Group VIII metal is Ni and / or Co, and the Group VIB metal is W and / or Mo. Based on the weight of the catalyst, the content of Group VIII metals, calculated as metal oxides, is 3%-15%, preferably 5%-10%, and the content of Group VIB metals, calculated as metal oxides, is 10%-30%, preferably 15%-25%.
[0016] In the method of the present invention, the hydrocracking catalyst contains 20%-50%, preferably 25-40%, of binder based on its weight.
[0017] In the method of this invention, the specific surface area of the hydrocracking catalyst is 350 m².2 / g-450m 2 / g, preferably 380m 2 / g-420m 2 / g, pore volume 0.35cm 3 / g-0.50cm 3 / g, preferably 0.38cm 3 / g-0.45cm 3 / g.
[0018] In the method of the present invention, the preparation method of the hydrocracking catalyst includes mixing BY heteroatom molecular sieve, binder and hydrogenation active metal to obtain hydrocracking catalyst, or molding BY heteroatom molecular sieve and binder first and then loading hydrogenation active metal to obtain hydrocracking catalyst.
[0019] The method of this invention includes a non-limiting method for preparing a hydrocracking catalyst, comprising the following steps: (1) BY heteroatom molecular sieve, binder and hydrogenated active metal are mixed in a certain proportion, and then a colloid solvent (e.g. nitric acid solution) is added to the mixture to make a slurry for kneading and extrusion molding; (2) The extruded product obtained in step (1) is dried and calcined to obtain a hydrocracking catalyst.
[0020] In the method of the present invention, the mass fraction ratio of BY heteroatom molecular sieve, binder and hydrogenated active metal (calculated as metal oxide) in the solid mixture in step (1) is 20%-40%: 25%-50%: 15%-35%; the concentration of the nitric acid solution is 5-30% by mass; the solid content of the slurry is suitable for extrusion molding to obtain a strip-shaped extruded product, preferably, the solid content of the slurry is 30-60% by mass.
[0021] In the method of this invention, the average particle size of the BY heteroatom molecular sieve in step (1) is 1.0 μm-3.0 μm, preferably 1.5 μm-2.5 μm; the specific surface area of the BY heteroatom molecular sieve is 750 m². 2 / g-900m 2 / g, preferably 800m 2 / g-850m 2 / g; Total pore volume is 0.36cm³ 3 / g-0.45cm 3 / g, preferably 0.38cm 3 / g-0.42cm 3 / g, wherein the mesoporous pore volume accounts for 25%-50% of the total pore volume, preferably 30%-40%.
[0022] In the method of the present invention, the BY heteroatom molecular sieve in step (1) has a typical FAU type topology, with B atoms in the Y molecular sieve framework, and the relative crystallinity of the BY heteroatom molecular sieve is 85%-105%, preferably 90%-100%.
[0023] In the method of the present invention, the silicon-to-aluminum ratio (SiO2 / Al2O3 molar ratio) of the BY heteroatom molecular sieve in step (1) is 5-20, preferably 8-15; in the BY heteroatom molecular sieve, the Na2O mass content is less than 0.5% by weight, preferably 0.05%-0.3%; the B atom content (in terms of oxide mass fraction) is ≤5.0%, preferably ≤3.0%.
[0024] In the heteroatom Y molecular sieve of the present invention, the pyridine infrared acid content of the heteroatom Y molecular sieve is 0.5 mmol / g-1.2 mmol / g, preferably 0.7 mmol / g-1 mmol / g; wherein, the Brønsted acid / Lylene acid (molar ratio) ratio is 0.1-35, preferably 3-20; and the content of medium-strong acid accounts for 60%-80%, preferably 65%-75%.
[0025] In the method of this invention, the adhesive mentioned in step (1) is γ-alumina, characterized by a specific surface area of 200 m². 2 / g-600m 2 / g, preferably 300m 2 / g-500m 2 / g; pore volume 0.5cm 3 / g-1.5cm 3 / g, preferably 0.8cm 3 / g-1.2cm 3 / g.
[0026] In the method of the present invention, in step (2), the extruded product is dried at 80℃-120℃ for 6h-12h, and then calcined at 400℃-500℃ for 1h-5h.
[0027] The preparation method of the BY heteroatom molecular sieve in this invention comprises the following specific steps: (a) Ammonium ion exchange of Y molecular sieve; (b) Perform hydrothermal treatment on the material obtained in step (a); (c) The material obtained in step (b) is processed by a mixed solution of ammonium fluorosilicate and boron atom precursor, and then filtered, washed, dried and calcined to obtain BY heteroatom molecular sieve.
[0028] In the BY molecular sieve preparation method of the present invention, the Y molecular sieve in step (a) can be prepared according to existing public technology or by using commercially available products.
[0029] In the BY molecular sieve preparation method of this invention, the specific surface area of the Y molecular sieve in step (a) is 750 m². 2 / g-900m 2 / g, preferably 800m 2 / g-850m 2 / g; Total pore volume is 0.35cm³ 3 / g-0.42cm 3 / g, preferably 0.38cm 3 / g-0.40cm 3 / g.
[0030] In the BY molecular sieve preparation method of the present invention, the average particle size of the Y molecular sieve in step (a) is 1.0 μm-3.0 μm, preferably 1.5 μm-2.5 μm.
[0031] In the BY molecular sieve preparation method of the present invention, the silicon-to-aluminum ratio (SiO2 / Al2O3 molar ratio) of the Y molecular sieve in step (a) is 4.5-6.0, preferably 5.0-5.5.
[0032] In the BY molecular sieve preparation method of the present invention, the Y molecular sieve in step (a) has a Na2O content of 9%-13% by weight, preferably 11%-12%.
[0033] In the preparation method of BY molecular sieve of the present invention, in step (a), Y molecular sieve and ammonium salt solution are subjected to ion exchange for 1-3 hours at 30℃-100℃, preferably 60℃-90℃, and the number of exchange times is 1-2.
[0034] In the BY molecular sieve preparation method of the present invention, the ammonium salt used in the ion exchange in step (a) is one or more of ammonium chloride, ammonium nitrate, ammonium sulfate, ammonium acetate, and ammonium oxalate. The concentration of the ammonium salt solution is 0.5 mol / L-2 mol / L, preferably 1 mol / L-1.5 mol / L. The solid-liquid ratio of the Y molecular sieve to the ammonium salt solution is 1:5-15 (g:mL), preferably 1:8-10 (g:mL).
[0035] In the BY molecular sieve preparation method of this invention, step (a) controls the Y molecular sieve to contain an appropriate amount of sodium ions. Based on the weight of the Y molecular sieve, the mass content of sodium ions, calculated as sodium oxide, is 2.8%-4.5%, preferably 3.5%-4.0%. An appropriate amount of Na ions has a stabilizing effect on the sodalite cages of the molecular sieve during the hydrothermal treatment of the Y molecular sieve, which is beneficial to the efficient retention of crystallinity of the molecular sieve in subsequent hydrothermal processes.
[0036] In the method for preparing BY molecular sieves of the present invention, the hydrothermal treatment in step (b) is a steam heat treatment: the material obtained in step (a) is contacted with steam at a temperature of 550℃-700℃ and a pressure of 0.05Mpa-0.3MPa for 1h-4h.
[0037] In the preparation method of BY molecular sieve of the present invention, in step (c), the material obtained in step (b) is treated with a mixed solution of ammonium fluorosilicate and boron atom precursor at 60℃-120℃, preferably 80℃-100℃, for 3h-5h. Then, the solid particles are filtered, washed, dried and calcined to obtain BY heteroatom molecular sieve.
[0038] In the BY molecular sieve preparation method of the present invention, the concentration of ammonium fluorosilicate in the mixed solution in step (c) is 0.02 mol / L-0.15 mol / L; and the concentration of boron atom precursor is 0.01 mol / L-0.05 mol / L.
[0039] In the BY molecular sieve preparation method of the present invention, the heteroatom precursor in step (c) is at least one of boric acid and ammonium fluoroborate.
[0040] In the BY molecular sieve preparation method of the present invention, the solid-liquid ratio of the molecular sieve material obtained in step (b) to the mixed solution in step (c) is 1:20-50 (g:mL).
[0041] In the BY molecular sieve preparation method of the present invention, the heteroatom Y molecular sieve product in step (c) is subjected to solid-liquid separation by filtration, washed with water until neutral, and the drying temperature is 80℃-120℃, and the drying time is 12h-24h; the calcination atmosphere is air, the calcination temperature is 400℃-500℃, and the calcination time is 2h-4h.
[0042] The BY heteroatom molecular sieve in the hydrocracking catalyst provided by this invention possesses characteristics such as a high Brønsted acid / Low acid ratio, a high proportion of moderately strong acids, high crystallinity, and abundant mesoporous channels, all of which are highly beneficial for the ring-opening conversion of polycyclic aromatic hydrocarbons in heavy oil feedstocks. The hydrocracking catalyst prepared by this invention exhibits advantages such as high reactivity, high product liquid yield, low hydrogen consumption, high aromatic potential in heavy naphtha, high smoke point in jet fuel, and low BMCI value and dry point in tail oil during vacuum oil hydrocracking. Detailed Implementation
[0043] The present invention will be further described in detail below with reference to specific embodiments. These embodiments are implemented based on the technical solution of the present invention, providing detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.
[0044] Unless otherwise specified, the experimental methods used in the following examples are conventional methods in the art. Unless otherwise specified, the experimental materials used in the following examples were purchased from conventional biochemical reagent stores. In this invention, the crystal structure and relative crystallinity of the molecular sieve were determined by XRD characterization; the average particle size of the molecular sieve was determined by a laser particle size analyzer (DLS); the acidity characteristics of the molecular sieve were determined by pyridine adsorption infrared spectroscopy; the elemental composition of the molecular sieve and catalyst was determined by ICP characterization; pore information was obtained by nitrogen adsorption-desorption testing at 77K using an ASAP 2420 automatic physical adsorption instrument; the reaction conversion rate was calculated from the actual boiling point data of the product; the BMCI determination method for the tail oil was: BMCI = 48640 / T + 473.7d - 456.8, where d is the density (15.6℃) and T is the average boiling point expressed in absolute temperature (K). Example 1
[0045] (1) Y molecular sieve (average particle size 1.7 μm, silica-alumina ratio 5.2, specific surface area 845 m²) 2 / g, pore volume 0.37cm 3 A mixture of sodium-containing Y molecular sieve (containing 12.1% Na2O) and a 1.0 mol / L ammonium nitrate solution at a solid-liquid ratio of 1:10 was prepared and subjected to ammonium ion exchange at 80℃ for 2 hours to obtain sodium-removed Y molecular sieve with a Na2O content of 3.9%.
[0046] (2) The desodium-free Y molecular sieve was contacted with water vapor at a temperature of 600℃ and a pressure of 0.1MPa for 2 hours to obtain the dealuminized Y molecular sieve.
[0047] (3) The dealuminated Y molecular sieve was mixed with a 0.05 mol / L ammonium fluorosilicate and a 0.05 mol / L boric acid mixed solution at a solid-liquid ratio of 1:30, treated at 80℃ for 3 h, filtered and separated, the solid was washed with water until neutral, dried at 100℃ for 12 h, and calcined at 500℃ for 2 h in air atmosphere to obtain the BY heteroatom molecular sieve. The properties of the BY heteroatom molecular sieve are as follows: the average particle size of the BY heteroatom molecular sieve is 1.7 μm; the specific surface area is 807 m². 2 / g, total pore volume is 0.42cm³ 3 / g, mesoporous pore volume accounts for 34.7% of the total pore volume; BY heteroatom molecular sieve exhibits typical FAU topological characteristic peaks. Using Y molecular sieve before heteroatom doping as a standard, the relative crystallinity of BY heteroatom molecular sieve is 102%; the silicon-to-aluminum ratio (SiO2 / Al2O3 molar ratio) of BY heteroatom molecular sieve is 15.2, the mass content of Na2O in BY heteroatom molecular sieve is 0.17%, and the content of B2O3 is 2.3%; the content of pyridine infrared acid in BY heteroatom molecular sieve is 1.04 mmol / g, of which the Brønsted acid / Low acid ratio is 27.5; the proportion of medium-strong acids is 73.5%.
[0048] (4) BY heteroatom molecular sieve, γ-alumina (specific surface area 460m²) 2 / g, pore volume 1.2cm 3 MoO3 powder and nickel nitrate were mixed in a dry mass ratio of molecular sieve: alumina: NiO: MoO3 of 30:49:5:16. Then, a 15% concentration of nitric acid solution was added to the mixture to prepare a catalyst slurry with a solid content of 50%, which was then kneaded and extruded into strips.
[0049] (5) The catalyst after molding was dried at 120°C for 3 hours and then calcined at 500°C for 3 hours in air to obtain a hydrocracking catalyst with strong ring-opening ability.
[0050] The hydrocracking catalyst provided in this embodiment, based on its weight, contains 30% BY heteroatom molecular sieve, 49% alumina, 5% NiO, and 16% MoO3, and is designated as A-1; the specific surface area of the hydrocracking catalyst is 391 m². 2 / g, pore volume 0.43cm 3 / g. Example 2
[0051] (1) Y molecular sieve (average particle size 1.7 μm, silica-alumina ratio 5.2, specific surface area 845 m²) 2 / g, pore volume 0.37cm 3 A mixture of 1 g (Na2O content 12.1%) and a 1.0 mol / L ammonium nitrate solution at a solid-liquid ratio of 1:10 was prepared and subjected to ammonium ion exchange at 80 °C for 2 h. The above operation was repeated once to obtain desodium-free Y molecular sieve with a Na2O content of 2.7%.
[0052] (2) The desodium-free Y molecular sieve was contacted with water vapor at a temperature of 650℃ and a pressure of 0.1MPa for 2 hours to obtain the dealuminized Y molecular sieve.
[0053] (3) The dealuminated Y molecular sieve was mixed with a 0.1 mol / L ammonium fluorosilicate and a 0.07 mol / L boric acid mixed solution at a solid-liquid ratio of 1:20, treated at 80℃ for 3 h, filtered and separated, the solid was washed with water until neutral, dried at 100℃ for 12 h, and calcined at 500℃ for 2 h in air atmosphere to obtain the BY heteroatom molecular sieve. The properties of the BY heteroatom molecular sieve are as follows: the average particle size of the BY heteroatom molecular sieve is 1.7 μm; the specific surface area is 794 m². 2 / g, total pore volume is 0.44cm³ 3 / g, mesoporous pore volume accounts for 45.5% of the total pore volume; BY heteroatom molecular sieve exhibits typical FAU topological characteristic peaks. Using Y molecular sieve before heteroatom doping as a standard, the relative crystallinity of BY heteroatom molecular sieve is 92%; the silicon-to-aluminum ratio (SiO2 / Al2O3 molar ratio) of BY heteroatom molecular sieve is 19.4, the mass content of Na2O in BY heteroatom molecular sieve is 0.09%, and the content of B2O3 is 3.8%; the content of pyridine infrared acid in BY heteroatom molecular sieve is 0.857 mmol / g, of which the Brønsted acid / Low acid ratio is 32.1; the proportion of medium-strong acids is 71.1%.
[0054] (4) BY heteroatom molecular sieve, γ-alumina (specific surface area 460m²) 2 / g, pore volume 1.2cm 3 MoO3 powder and nickel nitrate were mixed in a dry mass ratio of molecular sieve: alumina: NiO: MoO3 of 20:61:4:15. Then, a 15% concentration of nitric acid solution was added to the mixture to prepare a catalyst slurry with a solid content of 50%, which was then kneaded and extruded into strips.
[0055] (5) The catalyst after molding was dried at 120°C for 3 hours and then calcined at 500°C for 3 hours in air to obtain a hydrocracking catalyst with strong ring-opening ability.
[0056] The hydrocracking catalyst provided in this embodiment, based on its weight, contains 20% BY heteroatom molecular sieve, 61% alumina, 4% NiO, and 15% MoO3, and is designated as A-2; the specific surface area of the hydrocracking catalyst is 357 m². 2 / g, pore volume 0.44cm 3 / g. Example 3
[0057] (1) Y molecular sieve (average particle size 1.7 μm, silica-alumina ratio 5.2, specific surface area 845 m²) 2 / g, pore volume 0.37cm 3 A mixture of sodium-containing Y molecular sieve (containing 12.1% Na2O) and a 0.6 mol / L ammonium nitrate solution at a solid-liquid ratio of 1:10 was prepared and subjected to ammonium ion exchange at 80 °C for 2 h to obtain sodium-removed Y molecular sieve with a Na2O content of 4.4%.
[0058] (2) The desodium-free Y molecular sieve was contacted with water vapor at a temperature of 550℃ and a pressure of 0.1MPa for 1h to obtain the dealuminized Y molecular sieve.
[0059] (3) The dealuminated Y molecular sieve was mixed with a 0.03 mol / L ammonium fluorosilicate and a 0.03 mol / L ammonium fluoroborate mixed solution at a solid-liquid ratio of 1:40. The mixture was treated at 80°C for 3 h, filtered, and the solid was washed with water until neutral. It was dried at 100°C for 12 h and calcined at 500°C in air for 2 h to obtain the BY heteroatom molecular sieve. The properties of the BY heteroatom molecular sieve are as follows: the average particle size of the BY heteroatom molecular sieve is 1.7 μm; the specific surface area is 825 m². 2 / g, total pore volume is 0.40cm³ 3 / g, mesoporous pore volume accounts for 30.8% of the total pore volume; BY heteroatom molecular sieve exhibits typical FAU topological characteristic peaks. Using Y molecular sieve before heteroatom doping as a standard, the relative crystallinity of BY heteroatom molecular sieve is 99%; the silicon-to-aluminum ratio (SiO2 / Al2O3 molar ratio) of BY heteroatom molecular sieve is 12.1, the mass content of Na2O in BY heteroatom molecular sieve is 0.11%, and the content of B2O3 is 1.1%; the content of pyridine infrared acid in BY heteroatom molecular sieve is 1.13 mmol / g, of which the Brønsted acid / Low acid ratio is 18.2; the proportion of medium-strong acids is 67.4%.
[0060] (4) BY heteroatom molecular sieve, γ-alumina (specific surface area 460m²) 2 / g, pore volume 1.2cm 3 / g), ammonium metatungstate and nickel nitrate were mixed in a dry mass ratio of molecular sieve: alumina: NiO: WO3 of 40:37:6:17. Then, a 15% concentration of nitric acid solution was added to the mixture to prepare a catalyst slurry with a solid content of 50%, which was then kneaded and extruded into strips.
[0061] (5) The catalyst after molding was dried at 120°C for 3 hours and then calcined at 500°C for 3 hours in air to obtain a hydrocracking catalyst with strong ring-opening ability.
[0062] The hydrocracking catalyst provided in this embodiment, based on its weight, contains 40% BY heteroatom molecular sieve, 37% alumina, 6% NiO, and 17% WO3, and is designated as A-3; the specific surface area of the hydrocracking catalyst is 427 m². 2 / g, pore volume 0.35cm 3 / g. Example 4
[0063] The preparation steps of Y molecular sieve are the same as in Example 1, except that in step (3), amorphous silica-alumina fragments in the dealuminized Y molecular sieve are first removed by washing with acid solution, and then boron heteroatoms are loaded onto the Y molecular sieve by liquid phase equal volume impregnation method. The properties of the prepared BY heteroatom molecular sieve are as follows: the average particle size of the BY heteroatom molecular sieve is 1.7 μm; the specific surface area is 810 m².2 / g, total pore volume is 0.40cm³ 3 / g, mesoporous pore volume accounts for 30.0% of the total pore volume; BY heteroatom molecular sieve exhibits typical FAU topological characteristic peaks. Using Y molecular sieve before heteroatom doping as a standard, the relative crystallinity of BY heteroatom molecular sieve is 97%; the silicon-to-aluminum ratio (SiO2 / Al2O3 molar ratio) of BY heteroatom molecular sieve is 13.4, the mass content of Na2O in BY heteroatom molecular sieve is 0.10%, and the content of B2O3 is 2.3%; the pyridine infrared acid content of BY heteroatom Y molecular sieve is 0.950 mmol / g, of which the B acid / L acid ratio is 4.8; the proportion of medium strong acids is 63.3%.
[0064] The hydrocracking catalyst provided in Example 4, based on its weight, contains 30% BY heteroatom molecular sieve, 49% alumina, 5% NiO, and 16% MoO3, and is designated as A-4; the specific surface area of the hydrocracking catalyst is 384 m². 2 / g, pore volume 0.40cm 3 / g. Example 5
[0065] The preparation steps of Y molecular sieve are the same as in Example 2, except that in step (3), amorphous silica-alumina fragments in the dealuminized Y molecular sieve are first removed by washing with acid solution, and then boron heteroatoms are loaded onto the Y molecular sieve by liquid phase equal volume impregnation method. The properties of the obtained BY heteroatom molecular sieve are as follows: the average particle size of the BY heteroatom molecular sieve is 1.7 μm; the specific surface area is 781 m². 2 / g, total pore volume is 0.43cm³ 3 / g, mesoporous pore volume accounts for 42.8% of the total pore volume; BY heteroatom molecular sieve exhibits typical FAU topological characteristic peaks. Using Y molecular sieve before heteroatom doping as a standard, the relative crystallinity of BY heteroatom molecular sieve is 90%; the silicon-to-aluminum ratio (SiO2 / Al2O3 molar ratio) of BY heteroatom molecular sieve is 16.8, the mass content of Na2O in BY heteroatom molecular sieve is 0.12%, and the content of B2O3 is 3.8%; the content of pyridine infrared acid in BY heteroatom molecular sieve is 0.895 mmol / g, of which the Brønsted acid / Low acid ratio is 6.1; the proportion of medium-strong acids is 66.1%.
[0066] The hydrocracking catalyst provided in Example 5, based on its weight, contains 20% BY heteroatom molecular sieve, 61% alumina, 4% NiO, and 15% MoO3, and is designated as A-5; the specific surface area of the hydrocracking catalyst is 320 m². 2 / g, pore volume 0.44cm 3 / g. Example 6
[0067] The preparation steps of Y molecular sieve are the same as in Example 3, except that in step (3), amorphous silica-alumina fragments in the dealuminized Y molecular sieve are first removed by acid washing, and then boron heteroatoms are loaded onto the Y molecular sieve by liquid phase equal volume impregnation. The properties of BY heteroatom molecular sieve are as follows: the average particle size of BY heteroatom molecular sieve is 1.7 μm; the specific surface area is 830 m². 2 / g, total pore volume is 0.40cm³ 3 / g, mesoporous pore volume accounts for 31.9% of the total pore volume; BY heteroatom molecular sieve exhibits typical FAU topological characteristic peaks. Using Y molecular sieve before heteroatom doping as a standard, the relative crystallinity of BY heteroatom molecular sieve is 97%; the silicon-to-aluminum ratio (SiO2 / Al2O3 molar ratio) of BY heteroatom molecular sieve is 11.2, the mass content of Na2O in BY heteroatom molecular sieve is 0.14%, and the content of B2O3 is 1.1%; the content of pyridine infrared acid in BY heteroatom molecular sieve is 1.08 mmol / g, of which the Brønsted acid / Low acid ratio is 3.9; the proportion of medium-strong acids is 62.4%.
[0068] The hydrocracking catalyst provided in Example 6, based on its weight, contains 40% BY heteroatom molecular sieve, 37% alumina, 6% NiO, and 17% WO3, and is designated as A-6; the specific surface area of the hydrocracking catalyst is 422 m². 2 / g, pore volume 0.35cm 3 / g.
[0069] Comparative Examples 1-3 The hydrocracking catalyst provided in Comparative Example 1, based on its weight, contains 30% USY molecular sieve, 49% alumina, 5% NiO, and 16% MoO3, and is designated as C-1; the specific surface area of the hydrocracking catalyst is 379 m². 2 / g, pore volume 0.41cm 3 / g.
[0070] The hydrocracking catalyst provided in Comparative Example 2, based on its weight, contains 20% USY molecular sieve, 61% alumina, 4% NiO, and 15% MoO3, and is designated as C-2; the specific surface area of the hydrocracking catalyst is 339 m². 2 / g, pore volume 0.45cm 3 / g.
[0071] The hydrocracking catalyst provided in Comparative Example 3, based on its weight, contains 40% USY molecular sieve, 37% alumina, 6% NiO, and 17% WO3, and is designated as C-3; the specific surface area of the hydrocracking catalyst is 418 m². 2 / g, pore volume 0.36cm 3 / g.
[0072] The USY molecular sieve was purchased from Liaoning Tieling Desijie Chemical Co., Ltd., and has a specific surface area of 821 m². 2 / g, pore volume 0.41cm 3 The USY molecular sieve has a mesoporous content of 33.8% and a silica-to-alumina ratio (SiO2 / Al2O3 molar ratio) of 14.2. Based on weight, the Na2O content in the USY molecular sieve is 0.03%. The pyridine infrared acid content in the USY molecular sieve is 0.967 mmol / g, with a Brønsted acid / Low acid ratio of 3.0; the proportion of moderately strong acids is 61.4%. The specific surface area of the γ-alumina is 460 m² / g. 2 / g, pore volume 1.2cm 3 / g.
[0073] Evaluation Example 1 The hydrocracking catalysts prepared in the examples and the catalysts in the comparative examples were successively tested in a small fixed-bed unit for vacuum wax oil hydrocracking evaluation. The properties of the feedstocks are shown in Table 1. The evaluation unit adopted a single-stage series one-pass process flow. The first reactor was loaded with FF-66 hydrorefining catalyst (pressure 15.7 MPa, volumetric hourly space velocity 1.0 h⁻¹). -1 The nitrogen content of the refined wax oil was controlled to be ~5ppm. The second reactor was loaded with hydrocracking catalyst. The specific process conditions and evaluation results are shown in Table 2.
[0074] The properties of the crude oil used in the hydrocracking evaluation experiment are shown in Table 1:
[0075] Table 2
Claims
1. A method for hydrocracking wax oil, characterized in that: The wax oil raw material is treated with a hydrorefining catalyst and then reacted under the action of a hydrocracking catalyst. The hydrocracking catalyst contains 10%-50%, preferably 20%-40% BY heteroatom molecular sieve, based on its weight.
2. The method according to claim 1, characterized in that: The wax oil raw materials include atmospheric pressure wax oil and vacuum pressure wax oil, preferably vacuum pressure wax oil; the properties of the wax oil raw materials are: density range 0.85-0.95 g / cm³. 3 Distillation range 300℃-600℃, sulfur content 1.0%-3.0%, nitrogen content 500ppm-2000ppm, BMCI value 40-50.
3. The method according to claim 1, characterized in that: The properties of the hydrorefined oil obtained after hydrorefining of wax oil raw materials are as follows: nitrogen content <50ppm, preferably <20ppm; sulfur content <300ppm, preferably <200ppm.
4. The method according to claim 1, characterized in that: The hydrorefining reaction conditions are as follows: reaction pressure 10 MPa~20 MPa, preferably 12 MPa~16 MPa; reaction temperature 350℃~420℃, preferably 380℃~400℃; volume hourly space velocity of the hydrorefining catalyst 0.5 h⁻¹. -1 ~1.5h -1 0.8h is preferred -1 ~1.2h -1 The hydrogen-to-oil volume ratio is 500-1500, preferably 800-1200.
5. The method according to claim 1, characterized in that: The properties of the BY heteroatom molecular sieve are as follows: the silicon-to-aluminum ratio (SiO2 / Al2O3 molar ratio) is 5-20, preferably 8-15; the boron content, based on the mass of oxides, is ≤5.0%, preferably ≤3.0%, and even more preferably 0.5-2%.
6. The method according to claim 1, characterized in that: The hydrocracking catalyst contains 15%-35%, preferably 20%-30%, of hydrocracking active metal oxides based on its weight.
7. The method according to claim 6, characterized in that: The hydrogenation active metal is selected from Group VIII and / or Group VIB metals, wherein the Group VIII metal is Ni and / or Co, and the Group VIB metal is W and / or Mo. Based on the weight of the catalyst, the content of Group VIII metals, calculated as metal oxides, is 3%-15%, preferably 5%-10%, and the content of Group VIB metals, calculated as metal oxides, is 10%-30%, preferably 15%-25%.
8. The method according to claim 1, characterized in that: The hydrocracking catalyst contains 20%-50%, preferably 25-40%, of binder based on its weight.
9. The method according to claim 1, characterized in that: The specific surface area of the hydrocracking catalyst is 350 m². 2 / g-450m 2 / g, preferably 380m 2 / g-420m 2 / g, pore volume 0.35cm 3 / g-0.50cm 3 / g, preferably 0.38cm 3 / g-0.45cm 3 / g.
10. The method according to claim 1, characterized in that: The preparation methods of hydrocracking catalysts include mixing BY heteroatom molecular sieves, binders and hydrogenation active metals to obtain hydrocracking catalysts, or first molding BY heteroatom molecular sieves and binders and then loading hydrogenation active metals to obtain hydrocracking catalysts.
11. The method according to claim 11, characterized in that: The preparation method of hydrocracking catalyst includes the following: (1) BY heteroatom molecular sieve, binder and hydrogenated active metal are mixed in a certain proportion, and then a colloid is added to the mixture to make a slurry for kneading and extrusion molding; (2) The extruded product obtained in step (1) is dried and calcined to obtain a hydrocracking catalyst.
12. The method according to claim 1 or 10, characterized in that: The preparation method of BY heteroatom molecular sieves, with specific steps as follows: (a) Ammonium ion exchange of Y molecular sieve; (b) Perform hydrothermal treatment on the material obtained in step (a); (c) The material obtained in step (b) is processed by a mixed solution of ammonium fluorosilicate and boron atom precursor, and then filtered, washed, dried and calcined to obtain BY heteroatom molecular sieve.
Citation Information
Patent Citations
Hydrocracking catalyst and preparation and application thereof
CN118162208A